Georreferenciación de sistemas de suministros de energía eléctrica (2021)
In the following project it is estimated to define a procedure for the execution of future technical processes of georeferencing of electrical energy supplies which serves as a guide for companies interested in knowing the current state of their infrastructure. The document contains the statement of the problem, the objectives, the methodology, the scope and the expected results.